ASSESSMENT OF OXIDATIVE STRESS AND INFLAMMATORY MARKERS OF MEDICAL IMPORTANCE IN ORAL SQUAMOUS CELL CARCINOMA - Butt, SJ; Abbas, U; Arshad, A; Ahmad, B; Ashraf, A; Haseeb, M; Butt, AF; Rana, MA; Hafeez, MM (Biological and Clinical Sciences Research Journal, 2022)
There is an increased prevalence of oral squamous cell carcinoma (OSCC) globally but especially in Asian countries, and it is a well-known human malignant cancer. Oxidative stress markers might be helpful in diagnosis and to assess the progression of malignancy. The current analysis aimed to determine the altered levels of oxidative stress and inflammatory markers in oral squamous cell carcinoma. This research was conducted by the general pathology department of Institute of dentistry, CMH Lahore, from September 17, 2021, to January 17, 2022. Total of sixty age and sex matched participants were included in the study and further divided into two groups. In study group thirty confirmed cases of oral squamous cell carcinoma on histopathology were recruited. Oxidative stress markers were measured and statistically analyses done by using SPSS software version 25. The results showed increase levels of malondialdehyde, 8-hydroxy-2-deoxyguanosine, isoprostanes, interleukin-6 and tumor necrosis factor alpha as compared to the control group (p= 0.023, 0.001, 0.041, 0.000 and 0.033 respectively). Elevated levels of oxidative stress markers were found in patients of OSCC. That may lead to swift progression of disease and may increase mortality rate.